User Experience Evaluation and Service Priorities of the Ferizy App: Evaluasi Pengalaman Pengguna dan Prioritas Layanan Aplikasi Ferizy - Butar , Putri Stephany; Sumiati, Sumiati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The rapid development of digital technology has revolutionized public services by encouraging the adoption of online systems to improve efficiency and accessibility. Specific Background: In Indonesia, the Ferizy application was introduced company as an online ferry ticket booking system to support digital transformation in transportation. However, persistent user complaints indicate shortcomings in usability and service performance. Knowledge Gap: Despite its crucial role, comprehensive evaluations of Ferizy’s user experience and service performance using structured analytical models remain limited. Aims: This study aims to analyze the user experience of the Ferizy application using the HEART Framework and Importance Performance Analysis (IPA) to identify priority areas for improvement. Results: Findings reveal that all HEART dimensions scored below the 70% usability target, with Task Success at the lowest (55.18%). IPA results highlight seven attributes (H8, H12, T2, T3, T4, T7, T8) requiring immediate enhancement, particularly in ease of use, booking speed, and system stability. Novelty: The study integrates HEART and IPA approaches to provide a structured, user-centered evaluation of a national-scale transportation service. Implications: The results offer actionable insights for developers and policymakers to optimize digital service design and improve overall user satisfaction with public transportation applications. Highlights: Identifies key usability gaps in Ferizy app performance. Integrates HEART and IPA for structured user experience evaluation. Recommends focused improvements on ease of use and system stability. Keywords: Ferizy, HEART Framework, Importance Performance Analysis, User Experience, Service Improvement